Biochemical characterisation of ZFR, a regulator of splicing and RNA editing - Will, Alexander (The University of Edinburgh, 2023)
Eukaryotes use alternative splicing of pre-mRNA as a crucial mechanism to regulate their gene expression and expand the protein isoform repertoire. The essential human protein ZFR regulates alternative splicing and A-to-I editing of mRNA since many editing sites show lower editing levels upon knockdown of the ZFR homolog, Zn72D. Zn72D seems to act as the key regulator for most RNA editing sites in fruit flies, and these editing sites might require cooperative interaction between Zn72D and ADAR at the editing site. This work aimed to study the biological role of these proteins. Therefore, recombinant human ZFR was co-expressed with NF45 and used in an RNA Bind-n-Seq experiment (RBNS) performed by the Hogg lab to identify binding motifs. ZFR/NF45 constructs lacking zinc finger domains showed weak RNA binding activity than constructs with zinc fingers. In vitro verification of binding of RBNS-obtained motifs indicated that ZFR has a strong preference for dsRNA over ssRNA, suggesting that in vivo binding sites that determine alternative splicing sites are likely to contain substantial secondary structure. ZFR/NF45 binds dsRNA and RNA-DNA duplexes without sequence specificity. To gain a better insight into the mechanistic understanding of the role of ZFR in alternative splicing, structural studies of the various RNA-protein complexes might help us find out more about its precise biological role in regulating alternative splicing and A-to-I RNA editing. Therefore, stable in vitro RNA-protein complexes for biochemical and structural studies were produced using a 24-mer dsRNA and several protein components: ADAR, ZFR/NF45, and Zn72D/NF45. A-to-I RNA editing reactions were reconstituted using in vitro transcribed RNA and recombinant Drosophila ADAR and Zn72D/NF45 proteins. A poisoned primer extension and an EndoV assay were used to detect adenosine to inosine conversions in such in vitro RNA editing reactions. After establishing a protocol for successfully detecting in vitro adenosine to inosine conversions, the reason for the existence of Zn72D-dependent and Zn72D-independent RNA editing sites might be determined in the future using this assay.
Keywords: RNA editing; ZFR; Zn72D; Alternative splicing; biochemistry; protein purification; RNA binding; ADAR; structural biology; proteins; RNA-protein interaction; RNA processing